Enhanced Algorithms By Combining Gauss-Seidel And Newton-Raphson In Load Flow Analysis - Abouhasera, Mohamed Khalid Mohamed (Universiti Sains Malaysia, 2017)
Traditional load flow solution methods like Newton-Raphson has a great convergence characteristics with regards to its number of iterations and computing time, but suffers from poor convergence when used to solve ill-conditioned networks or if the starting initial values are far from solution. To overcome these concerns, we present enhanced algorithms for load flow analysis by combining Gauss-Seidel and Newton-Raphson methods that incorporate constant Jacobian to give a more dependable method with tolerable accuracy and shorter computation time.